2019
DOI: 10.1177/0020294019827336
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid GMR/IR probe to reduce the effects of lift-off

Abstract: Eddy current testing technique is being utilized in engineering, such as in nuclear steam pipe, aircraft and gas/oil pipeline, due to its sensitivity to small cracks and subsurface defects, immediate results, environmental friendliness, and use in examining complex sizes and shapes of substances. However, the lift-off noise due to irregular inspected materials surface, varying coating thicknesses, or movement of transducers extremely limits the implementation of eddy current testing in a non-disastrous testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The influence of permeability has been minimized by permeability-invariant-point at certain lift-off [14]. In contrast, the lift-off noise has been mitigated by response normalization and reference signals management [27], time-and frequencydomain differential response analysis [28], using a GMR-BC probe with an error compensation technique [29], and combining PCA and support vector machine [30]. In this research, the PCA features in Fig.…”
Section: A Wptect System Performance Analysismentioning
confidence: 98%
“…The influence of permeability has been minimized by permeability-invariant-point at certain lift-off [14]. In contrast, the lift-off noise has been mitigated by response normalization and reference signals management [27], time-and frequencydomain differential response analysis [28], using a GMR-BC probe with an error compensation technique [29], and combining PCA and support vector machine [30]. In this research, the PCA features in Fig.…”
Section: A Wptect System Performance Analysismentioning
confidence: 98%
“…These irregular signal peak points are called singular points, which reflect the propagation characteristics of ultrasonic waves in the metal. Previous studies have shown that the peak maximum after wavelet transform corresponds to the singularity of the signal [16]. Therefore, the amplitude and time of the peak maximum after wavelet packet transformation are defined as the third feature of the crack.…”
Section: Time Domainmentioning
confidence: 99%
“…Finally, the ECECT is used to measure lift-off in a range of approximately 1 mm to 5 mm, and the performance of the proposed method in non-linear cracks is assessed. Faraj et al [ 27 ] proposed a study on a hybrid giant magneto-resistance/infrared probe to minimize the influence of lift-off for detecting depth defects. The proposed method is verified experimentally, and the result shows that the impact of lift-off noise is highly reduced in the eddy current testing technique and enhances the sensor accuracy.…”
Section: Introductionmentioning
confidence: 99%